Visual representations of war in Polish and Scandinavian picturebooks. A metaphorical perspective - Hanna Dymel-Trzebiatowska (Problemy Wczesnej Edukacji)
The goal of the article is to show the potential of the war metaphor applied in the picturebook medium and reflect upon the cultural premises of its use. The analysed material includes three Polish and two Scandinavian books, published within four years, 2011–2014: Pamiętnik Blumki1 (Blumka’s Diary, 2011) by Iwona Chmielewska, Powieki (The Eyelids, 2012) by Michał Rusinek and Ola Cieślak, Ostatnie przedstawienie panny Esterki (Miss Esterka’s Last Performance, 2014) by Adam Jaromir and Gabriela Cichowska, Lejren (The Camp, 2011) by Oscar K. and Dorte Karrebæk and Krigen (The War, 2013) by Gro Dahle and Kaia Dahle Nyhus.